Maternal vitamin D and growth of under-five children: a systematic review and meta-analysis of observational and interventional studies - Amare Abera Tareke; Addis Alem; Wondwosen Debebe; Nebiyou Simegnew Bayileyegn; Melese Shenkut Abebe; Hussen Abdu; Taddese Alemu Zerfu (Taylor & Francis Group, 2022)
Background Even though previous systematic reviews have reported on the role of prenatal vitamin D on birth outcomes, its effect on child growth is poorly understood. Objective To synthesize a systematic summary of the literature on the effect of maternal vitamin D supplementation on the linear growth of under-five children. Method This study includes studies (both observational and interventional with a control group) that evaluated the effects of prenatal vitamin D status on child linear growth. The mean child length/length for age with 95% confidence interval (CI) was pooled as the weighted mean difference using a random-effects model. A funnel plot was used to assess potential publication bias. Results A total of 45 studies and 66 reports covering a total population of 44,992 (19,683 intervention or high vitamin D group, and 25,309 control or low vitamin D group) were analyzed. Studies spanned from 1977 to 2022. The pooled weighted mean difference was 0.4 cm (95% CI: 0.15-0.65). A subgroup analysis, based on vitamin D supplementation frequency, showed that mothers who supplemented monthly or less frequently had a 0.7 cm (95% CI: 0.2-1.16 cm) longer child. Supplementation with a dose of >2000 international units increased child length at birth. The weighted mean difference was 0.35 cm (95% CI: 0.11-0.58). Conclusion The evidence from this review shows that maternal supplementation of vitamin D is associated with increased birth length. This is apparent at higher doses, low frequency (monthly or less frequent), and during the second/third trimester. It appears that vitamin D supplementation during pregnancy is protective of future growth in under-five children. Clinical trials are needed to establish evidence of effectiveness for the frequency and dose of supplementation.